Rare-earth-free MnAl-C-Ni permanent magnets produced by extrusion of powder milled from bulk. (15th October 2020) - Feng, Le; Freudenberger, Jens; Mix, Torsten; Nielsch, Kornelius; Woodcock, Thomas George
Abstract: Rare-earth-free MnAl-C-Ni permanent magnets have been produced for the first time by extruding powders milled from bulk. The resulting materials, fabricated using different conditions, contained a large volume fraction (> 0.92) of the desired τ-phase. In terms of the maximum energy product, the best performance obtained for a whole, transverse section of the extruded material was (BH)max  = 46 kJm −3, and was (BH)max  = 49 kJm −3 for a sample taken from near the edge of this section. Analysis showed that this material was comparable to the long-established benchmark, comprising MnAl-C-based magnets extruded in industry from bulk or from gas-atomised powder. Such materials are no longer available. The microstructure of the materials produced here consisted of fine, recrystallised grains, which exhibited an <001> fibre texture with intermediate texture quality and of larger, non-recrystallised regions, which contained hierarchical twinning and a high density of defects. The volume fraction and size of the non-recrystallised regions was greatly reduced by decreasing the size of the initial powder particles. This led to a large increase in the squareness factor of the demagnetisation curve and consequently to the high (BH)max values observed. Graphical abstract: Image, graphical abstract